Variation of nano-ZnO/SBR modified asphalt features under photo-oxidative aging and optimization of the evaluation indexes based on rheological properties and chemical structure - Shengqian Zhao; Qinglong You; Jianming Ling; Jiake Zhang; Ekeoma Bridget Chineche; Jiaxing Wang (Case Studies in Construction Materials)
The purpose of this work is to propose suitable evaluation indices to understand and predict the photo-oxidative aging behavior of asphalt binders. Firstly, the low-temperature and photo-oxidative aging resistance of the asphalt was improved by using a combination of polymerized styrene butadiene rubber (SBR) and nano-ZnO (NZ). Subsequently, the aging evolution behavior of the asphalt binder was characterized at chemical-rheological scales using macro- and micro-testing tools. Then, mathematical statistics and Pearson correlation coefficients were used to optimize the evaluation indices and correlation analysis. Finally, the aging prediction equations for different binders were established based on a suitable index. The results show that photo-oxidative aging alters the chemical structure of asphalt, leading to an increase in its high-temperature deformation resistance and a decrease in its fatigue life and resistance to thermal cracking. Fatigue life at 2.5 % strain (Nf2.5 %), crossover frequency (fco), and Glover-Rowe (G-R) parameter were the most discriminating evaluation indexes for evaluating the effects of aging on asphalt fatigue performance, high temperature performance, and low temperature performance, respectively. The asphaltene content (Casp) is a key chemical indicator that responds to changes in the macroscopic characteristics of asphalt. The reliability of the aging prediction models using Casp exceeded 0.98. The predicted results indicate that as the polymer degrades during aging, the microchemical composition of the SBR binder eventually reaches a state similar to that of unmodified asphalt. NZ effectively inhibits the change from light to heavy asphalt chemical fractions and polymer degradation due to photo-oxidative aging.